1999
DOI: 10.1038/sj.gt.3300890
|View full text |Cite
|
Sign up to set email alerts
|

A novel endothelial cell-based gene therapy platform for the in vivo delivery of apolipoprotein E

Abstract: A major focus in gene therapy has been the use of recomand lesions at a young age. After transplantation of the binant viruses to deliver genes in vivo. Although this apoE secreting Pro 175 endothelial cells into apoEapproach shows much promise, there are many safety deficient mice, serum cholesterol levels were measured at concerns associated with the use of viral materials in the 2 week intervals. During the 3 months after the initiation of treatment of human diseases. Our alternative cell-based these experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…The normalization or reduction of the cholesterolemia after apoE3 gene transfer or normal bone marrow transplantation in apoE knockout mice has been demonstrated even in the absence of detectable levels of serum apoE. 10,27 The complex of these results definitely prove the hypothesis that very small amount of apoE are sufficient to enhance hepatic clearance of VLDL and IDL cholesterol in apoE knock-out mice. 27,32 Using fast protein liquid chromatography (FPLC) analysis we showed that the decrease in total serum cholesterol was accompanied by changes in the serum lipoproteins distribution.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The normalization or reduction of the cholesterolemia after apoE3 gene transfer or normal bone marrow transplantation in apoE knockout mice has been demonstrated even in the absence of detectable levels of serum apoE. 10,27 The complex of these results definitely prove the hypothesis that very small amount of apoE are sufficient to enhance hepatic clearance of VLDL and IDL cholesterol in apoE knock-out mice. 27,32 Using fast protein liquid chromatography (FPLC) analysis we showed that the decrease in total serum cholesterol was accompanied by changes in the serum lipoproteins distribution.…”
Section: Discussionmentioning
confidence: 91%
“…26 One possible explanation is the rapid cycling due to the high levels of cholesterol. 10 In fact, apoE protein could be quickly associated with lipids, taken up by the cells and transported to the tissues, thus resulting in a low serum concentration in these animals. In mice a large portion of the hepatic apoB (a ligand for the LDL-R along with apoE) is truncated (apo B48) and does not contain the LDL-R binding domain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our transfection studies are not directly relevant to the situation in vivo, as endothelium does not synthesize apoE, they do have implications for gene therapy; transfecting endothelial cells to express apoE may limit endothelial activation. Indeed, this approach prevents lesion development in apoE-deficient mice (34).…”
Section: Fig 6 Apoer2 Is Expressed In Huvecsmentioning
confidence: 99%